Sistem Pakar Sistem Pakar Diagnosis Hama Dan Penyakit Tanaman Bonsai Menggunakan Metode Forward Chaining - Nurhayati, Ismiya; Lestanti, Sri; Budiman, Saiful Nur (Program Studi Teknik Informatika Universitas Multi Data Palembang, 2022)
This study aims to build an expert system that can help determine quickly what pests or diseases attack bonsai plants based on symptoms that appear, especially in Blitar Nursery. Not only types of pests or diseases, this system also informs how to handle plants that are attacked by pests or diseases and how to prevent them. The method used in this study is the forward chaining method, the tracking process of this method is from symptom data, then matches the data with the IF part of the IF-THEN rule, if it is in accordance with the existing rules, then the rule will be executed to get a conclusion. This expert system was built using Bootstrap and the Hypertext Preprocessor (PHP) programming language with the Sublime Text text editor. Testing this expert system using black box and beta testing to IT experts and experts. The results of black box testing are 97.22% and beta test results are 85.2%, the conclusion that the system is feasible to use and can provide a diagnosis of pests or diseases in bonsai plants based on the symptoms given.